Komitas piano legacy - Sargsyan, Areg Villy (Musical Armenia, 2024)
The article explores the most fascinating realm of the great Armenian composer Komitas’ piano work, which, though limited in quantity, is distinguished by an unusual spirit of originality and innovation. To explain this quality, the author, first of all, convincingly unveils the essence of Komitas’s creative method. It is on the basis of a clear presentation of the artistic method that the article examines the content of the 6th volume of the Complete Works, encompassing all of the composer’s piano compositions. It also highlights the compositional features of his dances and various pieces from his student years, emphasizing the significance of his dances in the context of world musical art. It is also noteworthy that Areg Sargsyan, along with an interesting analysis of the music of this volume, presents the reader with research, compilation and editorial work, giving it due recognition. The article emphasizes the progressive and innovative nature of Komitas ’s piano compositions and methodically guides performers in studying them.